THE EFFECTIVENESS OF THE APPLICATION OF TEACHMINT LEARNING MEDIA BASED ON THE SAVI LEARNING MODEL TO IMPROVING IPAS LEARNING OUTCOMES - Yulsy Nitte; Kristina E Noya Nahak; Cornelia A. Naitili; Elsya Modok (Universitas Citra Bangsa, 2025)
The aim of this research was to determine the effectiveness of utilizing Teachmint media integrated with the SAVI learning model in improving Integrated Science and Social Studies (IPAS) learning outcomes among fifth-grade students of SD GMIT Oepura, Kupang City. This research employed a quantitative approach with a Quasi-Experimental design. The sample was selected using a purposive sampling technique, consisting two classes: Class V-A as the experimental group and Class V-B as the control group. The data collection technique consisted of a test comprising 20 multiple-choice questions. The application of the Direct Instruction model with a lecture method in the control class resulted in an average pre-test score of 50.48 and a post-test score of 62.62, indicating an improvement of 12.14 points. Meanwhile, the SAVI learning model supported by Teachmint media in the experimental class achieved an average pre-test score of 55.24, which increased to a post-test score of 87.86, reflecting an improvement of 32.62 points. The research findings were reinforced by hypothesis testing and t-test analysis of the post-test scores from both the control and experimental groups. The Independent Sample Test produced a significance value (2-tailed) for the t-test for Equality of Means of 0.000, which is less than the threshold of 0.05. This result confirms the acceptance of the alternative hypothesis (Ha), indicating a significant effect of the SAVI model supported by Teachmint media on IPAS learning outcomes, particularly for the theme